Lifestyle Marketing, Brand Personality, Brand Image, Customer Satisfaction, Customer Loyalty dan Impulse Buying - Kadek Adi Surya Pranantha; Nyoman Sri Subawa (Universitas Pendidikan Nasional, 2019)
ABSTRACTLifestyle is a person's lifestyle in the world expressed in his activities, interests, and opinions Widjaja (2009). Lifestyle describes a whole person in interacting in their environment. Lifestyle or lifestyle of humans today grow in tandem with the history of economic globalization and the transformation of consumption capitalism which is characterized by the mushrooming of shopping centers. Through many media that exploit the luxurious lifestyle around the development of food, fashion, and fun, humans indirectly need to adjust to these developments. Along with the lifestyle changes that are fixated on food, fashion, and fun, the learning centers began in Bali, especially in Badung Regency in recent years. The data analysis used in this study is CB-SEM (Covariance Based-Structural Equation Modeling) with the AMOS (Analysis of Moment Structure) program. The data used in this study are primary data obtained directly from the source where in this study the primary data that will be used is obtained from the questionnaire. The results of the study show that lifestyle marketing, brand personality, brand image, and customer satisfaction have a positive and significant influence on customer loyalty and impluse buying at Starbuck in Badung Regency.